Bond Strength of Self-Sensing Concrete (SSC) Incorporating Biomass Activated Carbon - Che Na'ii, Muhammad Alif Farhan; Mohd Jaini, Zainorizuan (Journal of Structural Monitoring and Built Environment, 2025)
Self-sensing concrete (SSC) has emerged as a multifunctional smart material that combines structural performance with self-monitoring capabilities, offering significant potential for structural health monitoring. In this study, biomass-activated carbon (BAC) was incorporated into SSC as a supplementary cementitious material to investigate its impact on bond strength. While BAC is known to enhance electrical resistivity and compressive strength, its effect on interfacial bonding behaviour has not been comprehensively evaluated. Therefore, this study aims to assess the bond strength of SSC incorporating BAC (SSC-BAC). The mix design of SSC-BAC is based on C25/30, which consists of ordinary Portland cement (OPC), silica fume, BAC, sand, and water. Cube specimens were prepared for the compression test. Meanwhile, rectangular and prism specimens were prepared for the slant shear and three-point bending tests. Experimental tests revealed that the compressive strength decreases as BAC content increases. A similar trend was also observed in the bond strength. The threshold for the compressive strength is 31.54 MPa produced by 1% BAC. Meanwhile, 3% BAC has the lowest acceptable bond strength. The findings of this study suggest that SSC-BAC exhibits a strong bonding behaviour, which is suitable for application in structural health monitoring.